Analisis Klaster K-Means Terhadap Kualitas Air Sungai di Kota Surakarta, Jawa Tengah - Yuli Handayani; Syafrudin Syafrudin; Suherman Suherman (Politeknik Statistika STIS, 2021)
This study aims to interpret water quality data collections on the Pepe River, Anyar River, Jenes River, Kedung Jumbleng River, Gajah Putih River, Brojo River, and Premulung River in Surakarta City, Central Java. The data was obtained from the results of water quality monitoring conducted by the Surakarta City Environmental Agency at 13 sampling locations in 2020. There are 12 parameters used, namely TSS, TDS, pH, BOD, COD, DO, P, NO3-N, NH3, NO2-N, Total Coliform, and Fecal Coliform. With the k-means algorithm, two clusters were obtained with differentiating parameters Total Coliform and Fecal Coliform. With a content of 3,790.050 MPN/100ml Total Coliform and 604,400 MPN/100ml Fecal Coliform, the Jenes Hilir River has poorer water quality than other rivers in terms of pollutant content of Total Coliform and Fecal Coliform.